PENGARUH EXPERIENTAL MARKETING TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Pada Pelanggan Maskapai Penerbangan Garuda Indonesia Branch office Semarang) - Edi Sudrajat; Naili Farida; Ngatno Ngatno (Universitas Diponegoro, 2016)
The purpose of this research was to determine the effect of Experiental Marketing Of Customer Loyalty throught Customer Satisfaction Garuda Indonesia Airlines. This location the research in Branch Office of Garuda Indonesia Airlines in Semarang. Population is all the passangers of Garuda Indonesia Airlines who used Garuda Indonesia Airlines more than twice one last year. This type of research is explanatory research. The sampling technique used non probability sampling technique and purposive sampling. This study uses qualitative and quantitative analysis techniques. Quantitative analysis using validity, reliability test, correlation coefficient, a simple regression analysis, the coefficient determination, tests of significance (t test), path analysis and sobel analysis. Based on the analysis result of the calculation, showed that there are direct effect from experiental marketing on customer satisfaction and customer loyalty, and customer satisfaction on customer loyalty. Beside result of this study revealed that indirect effect of experiental marketing toward customer loyalty mediated customers satisfaction.